Synthesis of conducting poly(5-carboxyindole)/Au nanocomposite: Investigation of structural and nanoscale electrical properties - Joshi L.; Prakash R. (My University, 2025)
We report, herein, redox chemical synthesis of processible nanocomposite of carboxylic acid functionalized conducting polymer, poly(5-carboxyindole) (5C-PIn) and gold metal nanoparticles. The method involves a reaction between aqueous dispersion of carboxyindole monomer and aqueous solution of HAuCl 4. The progress of the reaction is monitored by UV-visible spectroscopy and further nanocomposite is studied for structural, morphological, electrochemical and thermal properties. The concentration ratio of monomer and HAuCl4 is crucial to get desired morphology and uniformity of nanocomposite. The effect of the increasing concentration of gold salt is demonstrated with change in morphology and homogeneity of the nanocomposite. A uniform composite is formed using 1:2 mole ratio of HAuCl4 to monomer. Nanoscale electrical characterization of 5CPIn/Au nanocomposite is performed using current-sensing atomic force microscopy which exhibited a nonlinear and rectifying diode behavior with Al metal junction. Fluorescent spectral studies indicate that photoluminescence for the nanocomposite can be tuned from violet blue to yellow spectral range. The composite proves enormous potential in fabrication of nanoscale organic devices and organic optoelectronics. © 2013 Elsevier B.V.